A COMPARATIVE ANALYSIS OF ILLOCUTIONARY ACTS AND FELICITY CONDITIONS IN THE MAIN CHARACTERS OF ENCANTO AND RAYA AND THE LAST DRAGON (INFERENCE: Journal of English Language Teaching, 2026)
This study aims to (1) identify and categorize the types of illocutionary acts used by the main characters in Encanto and Raya and the Last Dragon; (2) analyze the fulfillment and violation of felicity conditions; and (3) compare the two films based on pragmatic features. Using a descriptive qualitative method, the research examines the utterances of Mirabel and Raya. The findings show four types of illocutionary acts such as representatives, directives, commissives, and expressives while declarations do not appear. Mirabel mainly uses representatives, whereas Raya frequently uses directives. In terms of felicity conditions, most utterances meet the propositional content condition, although Mirabel shows more violations in sincerity and essential conditions than Raya. The comparison also highlights cultural differences in their communicative styles. These findings imply that film dialogues can serve as effective authentic materials for developing students’ pragmatic competence, particularly in understanding how intentions and context shape meaning.
Keywords: Illocutionary Acts; Felicity Condition; Animated Film